A personalized approach-avoidance modification intervention to reduce negative body image. A placebo-controlled pilot study. (September 2020) - Glashouwer, Klaske A.; Timmerman, Joost; de Jong, Peter J.
Abstract: Background and objectives: Drive for thinness is considered an important factor in the onset and maintenance of negative body image and can be conceptualized as a motivational approach tendency towards thin bodies. The goal of this study was to test whether training thinness-related approach-avoidance tendencies is effective in improving body satisfaction using a personalized training with individuals' own body pictures. Methods: Undergraduate women scoring high on drive for thinness ( N  = 104) were randomly assigned to an experimental, placebo or no training control condition. The experimental training consisted of four training sessions in which participants pushed away thin versions of their own body pictures and pulled closer realistic pictures of themselves. The same stimuli were shown with 50/50 contingency in the placebo training. Results: The experimental training procedure did not show an effect on self-reported body satisfaction or drive for thinness after one session, four sessions, or one week later. While reaction time indices suggested a marginally significant change in approach-avoidance tendencies in the expected direction, this effect may have been driven by relatively strong thin-approach tendencies in the experimental condition before the start of the training. Limitations: High error rates limit the interpretability of the effects on approach-avoidance tendencies. Selection was based on a single item assessing drive for thinness. Conclusions: Taken together, our study did not provide evidence that training approach-avoidance tendencies is effective in improving negative body image. Highlights: Drive for thinness (DT) is considered a risk factor for negative body image. DT can be considered a motivational approach tendency towards thin bodies. We examined a novel approach-avoidance modification training with own body stimuli. Training approach-avoidance tendencies did not improve body image or DT.